Spatial Analysis of Shallow Sea Benthic Habitats Based on Sentinel-2A Imagery in the Southern Waters of Manado Bay - Putra Antou, Kevin; Rondonuwu, Ari B.; Rembet, Unstain N. W. J.; Modaso, Vivanda O. J.; Manu, Lusia; Kemer, Kurniati (Sam Ratulangi University, 2026)
The southern coastal region of Manado Bay is experiencing intensive development pressure alongside increasing tourism activities and marine space utilization. These conditions have the potential to cause degradation of shallow-water benthic habitats, which play a vital ecological role. This study aims to map and analyze the spatio-temporal changes of shallow-water benthic habitats in southern Manado Bay using Sentinel-2A satellite imagery as the primary data source. Analysis was conducted using Sentinel-2A imagery from the 2017-2023 period through stages of image pre-processing, water column correction, and unsupervised classification using the K-means algorithm. Evaluation of the classification results was performed using an error matrix to obtain overall accuracy and Kappa coefficient values. The results indicate that the overall accuracy ranged from 72-78% with Kappa coefficients between 0.60-0.71. Spatio-temporal analysis indicates a significant decline in live coral cover from 41.09% to 28.17% during the 2017-2023 period, accompanied by an increase in dead coral area and sand substrates. These findings demonstrate that Sentinel-2A imagery can be effectively utilized for monitoring the dynamics of shallow-water benthic habitats at a regional scale and has the potential to support sustainable coastal zone planning and management. Keywords: Change Detection, Coastal Management, Sentinel-2A, Benthic Habitat. Abstrak. Wilayah pesisir selatan Teluk Manado mengalami tekanan pembangunan yang intensif seiring dengan meningkatnya aktivitas pariwisata dan pemanfaatan ruang laut. Kondisi ini berpotensi menyebabkan degradasi habitat bentik perairan dangkal, yang memainkan peran ekologis vital. Studi ini bertujuan untuk memetakan dan menganalisis perubahan spasial-temporal habitat bentik perairan dangkal di selatan Teluk Manado menggunakan citra satelit Sentinel-2A sebagai sumber data utama. Analisis dilakukan menggunakan citra Sentinel-2A dari periode 2017-2023 melalui tahapan pra-pemrosesan citra, koreksi kolom air, dan klasifikasi tanpa pengawasan menggunakan algoritma K-means. Evaluasi hasil klasifikasi dilakukan menggunakan matriks kesalahan untuk mendapatkan akurasi keseluruhan dan nilai koefisien Kappa. Hasil menunjukkan bahwa akurasi keseluruhan berkisar antara 72-78% dengan koefisien Kappa antara 0,60-0,71. Analisis spasial-temporal menunjukkan penurunan signifikan pada tutupan karang hidup dari 41,09% menjadi 28,17% selama periode 2017-2023, disertai dengan peningkatan luas karang mati dan substrat pasir. Temuan ini menunjukkan bahwa citra Sentinel-2A dapat dimanfaatkan secara efektif untuk memantau dinamika habitat bentik perairan dangkal pada skala regional dan berpotensi mendukung perencanaan dan pengelolaan zona pesisir yang berkelanjutan. Kata kunci: Deteksi Perubahan, Pengelolaan Pesisir, Sentinel-2A, Habitat Bentik